Development of Biology Item Test Based on Science Literacy for Senior High School Students Class X Semester 1 - Zulyusri Zulyusri; Ramadhan Sumarmin; Miswati Miswati (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The purpose of this study was to develop evaluation tools in the form of learning about science literacy based biology subjects for class X semester 1. The type of this research is research and development, with a preparatory study design, prototype, one to one, small group and field tests. Small scale pilot study subjects were 20 students of SMAN 1 Bukit Sundi, and wide-scale trials were 64 students of SMAN 1 Gunung Talang. Product-based research is a matter of scientific literacy that includes three indicators of votes with four component aspects that owned the aspect of the context, content, processes and attitudes. The results of scientific literacy progression based this matter indicates that the matter developed valid, reliable and high level of practicality. This is demonstrated by the average validity showed extremely valid criteria. The effectivity of instruments is indicated by the student's ability to answer questions on indicators 2 and 3 which is a matter that demands high reasoning. Practicality instruments indicated by the positive response by teachers and students.